Total Physical Response (TPR) Untuk Meningkatkan Teknik Maharah Al-Kalam Pada Siswa Madrasah Ibtidaiyah - Chasanah, Rodifatul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Teach Arabic to motivated Arabic learning students in tpr. While usually thought of as a powerful language learning approach for beginning students, TPR actually has great potential for learners at any level of ability. The basic idea behind Total Physical Response is that a language learner learns to hear something in the language and then physically respond to it. This method was designed to accelerate listening comprehension of a foreign language by having subjects give a physical response when they heard aforeign utterance. This suggested that perhaps listening training should be continued for a long time without an attempt to speak before the student is asked to make any utterance in the foreign language.Key note : Total Physical Response, Maharah Al-Kalam di Madrasah Ibtidaiyah